2019
DOI: 10.22207/jpam.13.2.61
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Aspergillus fumigatus Biofilm and Cytotoxicity Study of Natural Compound Cis-9-Hexadecenal

Abstract: Clinical limitations and drug-resistance are the basis of the search for new antifungal therapeutics against biofilm forming pathogen Aspergillus fumigatus. Cis-9-hexadecenal is a natural compound present in various plants extracts, but its antifungal activity against A. fumigatus is still unexplored. The aim of present study was to evaluate the antifungal efficacy of cis-9-hexadecenal on A. fumigatus, specifically its biofilm and to assess its cytotoxicity. Broth micro-dilution method revealed that cis-9hexad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The biofilm of A. fumigatus was cultured in a 12-well polystyrene plate at calculated IC 50 of isoeugenol to analyse its effect (Manavathu et al 2014 ). To check biofilm eradication property of isoeugenol, biofilm was fully grown on 12-well polystyrene plate for 48 h and then, treated with IC 50 of isoeugenol for another 24 h (Hoda et al 2019 ; Sav et al 2018 ). To visualise the effect of isoeugenol, scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM) were performed and samples were processed as described by González-Ramírez et al ( 2016 ), with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The biofilm of A. fumigatus was cultured in a 12-well polystyrene plate at calculated IC 50 of isoeugenol to analyse its effect (Manavathu et al 2014 ). To check biofilm eradication property of isoeugenol, biofilm was fully grown on 12-well polystyrene plate for 48 h and then, treated with IC 50 of isoeugenol for another 24 h (Hoda et al 2019 ; Sav et al 2018 ). To visualise the effect of isoeugenol, scanning electron microscopy (SEM) and confocal laser scanning microscopy (CLSM) were performed and samples were processed as described by González-Ramírez et al ( 2016 ), with minor modifications.…”
Section: Methodsmentioning
confidence: 99%
“…The qualitative measurement of absorption, distribution, metabolism, excretion, and toxicity profile of selected compounds were predicted by using SwissADME program ( http://www.swissadme.ch/index.php ) (Hoda et al., 2019 ). The major ADME-Tox properties parameters include Molecular weight, H-bond acceptor, H-bond donors, Predicted octanol/water partition coefficient (MLogP), Total Polar Surface Area (TPSA), Lipinski (drug likeness), GI absorption, BBB permeant, Bioavailability score.…”
Section: Methodsmentioning
confidence: 99%
“…The computational study has reported C-9-H as a stable compound at varied conditions. 17 In the docking analysis, low binding energy of −4.95 kcal/mol was observed which was stabilized by hydrophobic interaction and hydrogen bond between C-9-H and the amino acid residues of PKS protein. The hydrogen bonds were formed at Thr-264 and Ser 171 residue of PKS active domain ( Figure 10).…”
Section: Transmission Electron Microscopymentioning
confidence: 94%
“…18 It has been observed that C-9-H inhibited biofilm formation in A. fumigatus and was not cytotoxic to human normal lung epithelial cell line L-132. 17 ADME/Tox study has also revealed that C-9-H is a stable compound at varied physiological conditions and is safe for human consumption. 17 It has been described as an aliphatic long-chain volatile compound that helps in fatty acid degradation and has characteristic strong fragrance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation